2003
DOI: 10.2460/ajvr.2003.64.813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical administration of 1% morphine sulfate solution on signs of pain and corneal wound healing in dogs

Abstract: Topical use of 1% MSS in dogs with corneal ulcers provided analgesia and did not interfere with normal wound healing. Both mu and delta opioid receptors were identified in normal corneas of dogs, although the mu receptors were present only in small numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
95
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(105 citation statements)
references
References 25 publications
9
95
0
1
Order By: Relevance
“…For all treatment protocols, this initial increase in corneal sensitivity was followed by a steady decrease (Table 1).The magnitude and significance of the initial increase and subsequent decrease is different between drugs, but this trend is consistently observed for each specific antiinflammatory drug evaluated.The control of corneal pain has limited options, as topical sodium channel blockers, such as proparacaine and tetracaine, are not acceptable due to their limited duration of activity and epitheliotoxic effects (Grant and Acosta, 1994;Herring et al, 2005;Venturi et al, 2016). Topical morphine has been shown to provide acceptable analgesia without a delay of corneal epithelialization (Peyman et al, 1994;Stiles et al, 2003;Clark et al, 2011); however, the corneal analgesic effectiveness in dogs has recently come into question (Thomson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For all treatment protocols, this initial increase in corneal sensitivity was followed by a steady decrease (Table 1).The magnitude and significance of the initial increase and subsequent decrease is different between drugs, but this trend is consistently observed for each specific antiinflammatory drug evaluated.The control of corneal pain has limited options, as topical sodium channel blockers, such as proparacaine and tetracaine, are not acceptable due to their limited duration of activity and epitheliotoxic effects (Grant and Acosta, 1994;Herring et al, 2005;Venturi et al, 2016). Topical morphine has been shown to provide acceptable analgesia without a delay of corneal epithelialization (Peyman et al, 1994;Stiles et al, 2003;Clark et al, 2011); however, the corneal analgesic effectiveness in dogs has recently come into question (Thomson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To prevent disturbing the dogs, the investigator was distant from the dogs during the measurement of pain score and eye blink frequency. CTT was measured by use of a Cochet-Bonnet aesthesiometer (Luneau ophtalmologie, Chartres Cedex, France) [11,21,23] following the evaluation of pain score and eye blink frequency. CTT measurements were conducted in the dogs sitting or in sternal recumbency with minimum head restraint or eyelid manipulation.…”
Section: Scoring Of Pain and Examinationsmentioning
confidence: 99%
“…one of them, morphine sulfate, is often used systemically to control pain, but has the potential for undesirable side effects. on the other hand, it is demonstrated that topical use of morphine relieves pain associated with corneal wounds in dogs [21] and rats [22]. Additionally, morphine did not cause a delay in corneal wound healing when it was used topically [21].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A central corneal epithelial wound was made as described previously (Stiles et al, 2003). Each dog was anesthetized with an intramuscular injection of ketamine hydrochloride (10 mg/kg) and xylazine (6 mg/kg) and with topical 1% lidocaine hydrochloride.…”
Section: Corneal Epithelial Woundmentioning
confidence: 99%